ANALISIS KEPUASAN ANGGOTA KOPERASI SERBA USAHA MADANI KOTABARU DENGAN METODE IPA (IMPORTANCE PERFORMANCE ANALYSIS) - - Rosida (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The objectives of this research are (1) to determine member satisfaction of ‘Madani’ Business Multipurpose Cooperation, Kotabaru based on the level of need and level of performance in the deminsions of direct evidence (tangible), reliability, responsiviness, assurance and empathy, (2) to determine which attributes belong to the main priority and maintained, or the excessive low priority, (3) to determine the width of the gap or gap between the importance and the performance of services. This type of this research was descriptive quantitative. In this research compared the level of need with the level of performace in producing satisfaction. Data were collected using questionnaires, and the samples of 121 cooperative members were selected by accidental sampling. Data analysis used IPA (Importance Performance Analysis) and gap analysis. The analysis result of the suitability level of the lowest attributes of the service quality was responsiveness (responsiveness) with the attribute of quick responsiveness in responding to complaints/problems (87.71%), and the highest dimension was direct evidence (tangible) in the attributes of cleanliness and tidiness of office and employees (101.10%).